Analisis Kualitas Pendanaan Program Pensiun Manfaat Pasti pada Dana Pensiun Bank Pembangunan Daerah NTT - Benyamin, Karmi Yulet; Kiak, Novi Theresia; Tungga, Cicilia A. (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to determine the quality of funding for the Defined Benefit Pension Program produced by the NTT Regional Development Bank Pension Fund using a quantitative descriptive approach method. This type of research is field research. The informants used in this research consisted of the Head of Finance and Accounting and the Head of Investment and Funding. Data was collected using field research techniques, interviews and documentation. The data sources in this research are primary and secondary data sources. Based on the research results, it shows that the NTT Regional Development Bank Pension Fund is experiencing a funding deficit. The results of the research show that the analysis shows a decrease in the quality of funding for the NTT Regional Development Bank Pension Fund from Level I (Funded) in June and December 2023 to Level II (Partially Funded) in June 2024 with a total funding ratio of 97.89% and a solvency ratio of 102 .24% which is due to the increase in the amount of actuarial liabilities which is greater than the assets for Funding. The declining funding ratio reflects a deficit in assets to cover actuarial liabilities, while the decline in solvency highlights the challenges in maintaining the ability to face long-term risks so that more attention is needed in increasing transparency and ensuring accountability in every decision taken.